Law and Post-Truth: Critical Constructivism as an Ideal Legal Reasoning Method on Indonesia's Post-Truth Era Society - Josua Navirio Pardede; Piere Hugo Poluakan (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2021)
This article aims to look at the current reality, which is marked by the proliferation of post-truth phenomena in the community, marking the many developments in the views and perspectives of each individual who considers something as an absolute truth by shifting the existence of facts, data. , and reality. This is the reality of challenges in the current era, so that in responding to the challenges posed by the post-truth era, scientific frameworks, including law as one of the main components that interact directly with society must try to avoid the formation of analyzes that lead to absolute truth. This article is the result of legal research using secondary legal materials. The results show that, critical constructivism as a method of reasoning that determines the process of legal reasoning, is able to prove its never-ending thought process by placing a gap between materialism and idealism, and its epistemological aspects provide a simultaneous relationship between empiricism and rationalism. The results of legal interpretation through the pattern of critical constructivism will continue to be criticized as long as the results of the interpretation cannot show the truth, this process will obtain an analysis result that will never lead to the absolute truth inherent in post-truth. world.